2002
DOI: 10.1111/j.1749-6632.2002.tb02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward Mechanism‐based Antioxidant Interventions

Abstract: It is generally accepted that one of the major and important contributions to skin aging, skin disorders, and skin diseases results from reactive oxygen species. More than other tissues, the skin is exposed to numerous environmental chemical and physical agents, such as ultraviolet light, causing oxidative stress. Accelerated cutaneous UV-induced aging, photo aging, is only one of the harmful effects of continual oxygen radical production in the skin. Interestingly, our ELISA assays of 8-oxo-2'-deoxyguanosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 14 publications
3
15
0
1
Order By: Relevance
“…As demonstrated in our data, vitamin E appears to react mostly as enzyme regulator and less as free radical antagonist. Our results are also in accordance with those on superoxide dismutase and Cu,Zn-superoxide dismutase, where a reduction of their activity was found in various cancer tissues compared with normal tissues [24,38,39]. The differences in the behavior of enzymic and nonenzymic antioxidants in the epidermis and dermis were also noticed by other researchers [18,19].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As demonstrated in our data, vitamin E appears to react mostly as enzyme regulator and less as free radical antagonist. Our results are also in accordance with those on superoxide dismutase and Cu,Zn-superoxide dismutase, where a reduction of their activity was found in various cancer tissues compared with normal tissues [24,38,39]. The differences in the behavior of enzymic and nonenzymic antioxidants in the epidermis and dermis were also noticed by other researchers [18,19].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is assumed that the local accumulation of lipophilic LMWA maybe induces toxicity to skin tissues and that the protective mechanism of the body does not respond under these conditions. Kagan et al [38] demonstrated that in accelerated cutaneous UV-induced aging the production of 8-oxo-2′-deoxyguanosine was independent from the vitamin E status. As demonstrated in our data, vitamin E appears to react mostly as enzyme regulator and less as free radical antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Solar radiation increases 8OHDG in the skin and humans receiving indoor tanning UV radiation incur DNA damage (The International Agency for Research on Cancer Working Group on artificial ultraviolet light and skin, 2007). ROS-induced accumulation of 8OHDG DNA damage occurs in skin of old, but not young, mice, indicating a role in photoaging(Kagan et al, 2002). Ang1 protects against nuclear DNA damage,…”
mentioning
confidence: 99%
“…Vitamin E, a known antioxidant, inhibits lipid peroxidation and interferes with the process of cytokine-mediated cytotoxicity by acting as a free oxygen scavenger (12,13). It has also been shown that lipid peroxidation is involved in the cytotoxic effects of cytokines on rat islets and that the inhibition of this process protects islet beta cells from the combined cytotoxic effects of interleukin 1, tumor necrosis factor and interferon gamma (14).…”
Section: Introductionmentioning
confidence: 99%